Combination Effectiveness of Listening to Music and Listening Murottal to Reduce Postpartum Depression - Rahayu Sumaningsih; Nurlailis Saadah; Teta Puji Rahayu; Sulikah; Budi Yulianto (International Journal of Advanced Health Science and Technology, 2022)
It was reported that 50% of Postpartum women experience symptoms of stress/anxiety known as postpartum blues, with the level of depressive symptoms continuing to increase to postpartum depression. This condition cannot be cured without clinical intervention. Music iscreated to influence the psychological condition of humans, as well as to provide a sense of security, comfort and fun. To describe the effect of a combination of natural and murotal music to reduce postpartum depression. The contribution of this study is to explain the effect of the combination of natural and murottal music to reduce postpartum depression. This study used a Quasi-Experiment method through pretest-posttest design with a control group and a treatment group. In this case, the intervention group was given a combination of natural and murottal music therapy, in which each intervention was given for 30 minutes for three consecutive days. The number of samples involved was 60 people who were divided into 2 groups of postpartum mothers. The intervention group consists 30 people, while the control group consists 30 people. Data was collected using the EPDS (Edinburgh Postnatal Depression Scale) questionnaire. Data analysis used independent t-test. Results: There were 9 mothers with mild depression and 21 moderate depressions in the intervention group. On the other hand, there were 17 normal mothers and 13 moderately depressed mother in the post-intervention group with t test value of 27.17 and sig of (p) 0.00 v(value) 0.36. Meanwhile in the control group, there were 1 (one) normal mother, 27 mothers who had mild depression and 2 mothers who had moderate levels. There were 19 mothers with low depression and 11 mothers with moderate depression. The results of the t-test obtained 22.13 with sig(p) 0.01 v(value) 0.001. There was an effect of music therapy on the reduction in the incidence of postpartum depression which was very significant after three days of being given music therapy. There was an increase in the level of depression by two levels higher from pre to post in the control group. Furthermore, the results of the t-test on the postpartum blues pretest and posttest showed that there was a significant difference in the incidence of postpartum blues between the control and intervention groups after the intervention period. There is a difference in the value of t 5.04 sig (p) 0.01, even though the value is smaller than t table (0.05). The difference obtained shows that the control group has a risk of experiencing postpartum blues by 2 (two) times compared to the intervention group. Music therapy was given to all postpartum primiparous mothers immediately after delivery. Health services need to prepare facilities and human resources to provide relaxation therapy, namely music therapy as an alternative therapy.